Slag formation during combustion of biomass fuels - Öhman, Marcus; Nyström, Ida-Linn; Gilbe, Carl; Boström, Dan; Lindström, Erica; Boman, Christoffer; Backman, Rainer; Hedman, Henry; Samuelsson, Robert; Burvall, Jan; Shaojun, X (Luleå tekniska universitet, Energivetenskap, 2009)
Slag and ash deposition problems have more than occasionally been observed in biomass fueled plants in general and especially in pellet fired plants. These problems could lead to reduced accessibility as well as performance of the combustion appliances. Slag formation including measures for prevention and prediction during combustion of biomass fuels has been studied by the research groups at Luleå University of Technology, Umeå University, Energy Technology Center and Swedish University of Agricultural Sciences for about one decade know. Several (about 40) different biomass fuels/fuel mixtures have been studies and many different fuel additives/co-combustion fuels have been used to combat slag formation. About 25 scientific papers and 10 technical reports have been published by the research groups within the topic of slag formation during combustion of biomass fuels. The general experiences and conclusions of our research within the area will be presented. Godkänd; 2009; 20090822 (ohmmar)